Prefrontal cortex contribution in transitive inference task through the interplay of beta and gamma oscillations - Fabio Di Bello; Valentina Mione; Pierpaolo Pani; Emiliano Brunamonti; Stefano Ferraina (Communications Biology)
Abstract Transitive inference allows people to infer new relations between previously experienced premises. It has been hypothesized that this logical thinking relies on a mental schema that spatially organizes elements, facilitating inferential insights. However, recent evidence challenges the need for these complex cognitive processes. To dig into the neural substrate driving TI cognitive processes, we examine the role of beta and gamma local field potential bands in the prefrontal cortex of 2 monkeys. During the inferential problem-solving period, we discover a tight link between beta and gamma bands modulation and TI complexity. This correlation diminishes its strength before initiating the motor response, indicating the chosen item. Notably, while the beta band maintains a constant relationship with TI performance throughout the trial, the gamma band shows a flexible relationship. This research highlights the role of beta and gamma interplay in cognitive computations when solving TI problems.